Shahadah 'Ilmy; Integrating Fiqh and Astronomy Paradigm in Determining The Arrival of Lunar Months in Indonesia - Muh. Arif Royyani; Abdul Mufid; M. Ihtirozun Ni’am; Alfian Qodri Azizi; Achmad Azis Abidin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
Formulating the fixed methodology for determining the beginning of Ramadan month and Islamic Feast in Indonesia is still ongoing. This article attempts to offer an integration between sharia and scientific views through 1) the concept of shahadah (witnessing) in the paradigm of fiqh and astronomy, and 2) the integration of those paradigms in determining the beginning of lunar months, particularly Ramadan and Syawal. This study uses qualitative methods in gaining the data then analyzes it using the approach of Miles & Huberman on interdisciplinary study. The findings of this research are as follows: 1) the concept of shahadah in the paradigm of fiqh is based on religious vows and factual evidence, while the astronomical paradigm perceives it from the certainty of external factors (weather, climate, environment, etc.). 2) Integration of those two paradigms results in better methods. It can turn the shahadah into the quality of qat'i (fixed) while the astronomic perspective gains more legitimacy. The integration is therefore called shahadah-'ilmi which potentially integrates the criteria of crescent visibility (imkan al-rukyah) in Indonesia to minimize the common occurrence on differences in determining those days. (Penetapan awal bulan Ramadhan dan Hari Raya di Indonesia masih terus dirumuskan metodologinya. Artikel ini menawarkan integrasi antara sudut pandang syari’ah dan saintifik melalui kajian atas 1) konsep syahadah dalam paradigma fiqh dan astronomi, 2) integrasi paradigma fiqh dan astronomi dalam menetapkan awal bulan Islam, utamanya Ramadhan dan Syawal. Penelitian ini menggali data dengan metode kualitatif kemudian menganalisisnya dengan pendekatan Miles & Huberman tentang kajian interdisipliner. Temuan penelitian ini adalah sebagai berikut: 1) Konsep shahadah dalam paradigma fiqh adalah penglihatan yang disertai dengan sumpah dan bukti faktual, sementara dalam paradigma astronomi, shahadah didasarkan pada kepastian ukuran dari faktor–faktor eksternal meliputi cuaca, iklim dan lingkungan. 2) Integrasi dua paradigma tersebut menghasilkan metode yang lebih baik dalam penentuan awal Ramadhan dan Syawal. Shahadah dalam sudut pandang fiqh berubah menjadi qath’i (pasti), sementara hasil persaksian astronomi semakin memperoleh legitimasi. Integrasi kedua paradigma melahirkan konsep shahadah-'ilmi yang dapat digunakan untuk menentukan tampaknya hilal (rukyah hilal) awal Ramadhan dan Syawal di Indonesia sehingga perbedaan yang kerap terjadi dalam menentukan dua awal bulan tersebut dapat diminalisir.)